2022
DOI: 10.1159/000526246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dimensions and Functions of Crystalline Lens in High Myopia Using CASIA2 Optical Coherence Tomography

Abstract: Introduction: Crystalline lens is the major dioptric component and varies with refractive status. In this study, we aim to evaluate the changes of dimensions and functions of crystalline lens in high myopia and its correlated variables using CASIA2 swept-source optical coherence tomography (SS-OCT). Methods: One hundred and thirty eligible eyes of myopic patients from 18-40 years old were enrolled and divided into low-to-moderate myopia (LMM) and high myopia (HM) groups according to spherical equivalent (SE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These results agree with previous studies and provide more evidence of the classic theories of accommodation. 12,[24][25][26] The anterior radii of curvature have been reported to decrease by 0.6-0.8 mm per dioptre change in accommodative stimulus when measured with the OCT. 12,25,27,28 The corresponding changes in the present study were in the same direction but of a smaller magnitude, which may have been caused by differences in the refractive status of the enrolled participants, 29 accommodative stimuli 30 and measuring methods. The results of the present study suggest that 2D viewing would not induce dynamic changes in the eyes.…”
Section: Discussionmentioning
confidence: 42%
“…These results agree with previous studies and provide more evidence of the classic theories of accommodation. 12,[24][25][26] The anterior radii of curvature have been reported to decrease by 0.6-0.8 mm per dioptre change in accommodative stimulus when measured with the OCT. 12,25,27,28 The corresponding changes in the present study were in the same direction but of a smaller magnitude, which may have been caused by differences in the refractive status of the enrolled participants, 29 accommodative stimuli 30 and measuring methods. The results of the present study suggest that 2D viewing would not induce dynamic changes in the eyes.…”
Section: Discussionmentioning
confidence: 42%
“…The traditional feature extraction of heavy points adopts a manual visual method. This algorithm is simple and easy to implement, and there may be some unexpected errors in the extraction process due to subjective influence [8]. In tilt monitoring, fixed control targets or special extraction methods are usually used to get the characteristics of key points.…”
Section: Comparative Study On Features Of Points With the Same Namementioning
confidence: 99%
“…E yes with high myopia exhibit many specific characteristics in ocular biometry. The anterior chamber is deeper, 1,2 the lens and choroidal thickness are thinner, [3][4][5] and posterior vitreous detachment progresses faster in eyes with high myopia than in eyes without high myopia. [6][7][8] Corneal biometry studies demonstrated that the corneal curvature is also flatter and the corneal thickness is thinner in highly myopic eyes.…”
mentioning
confidence: 99%